Active Commuting and the Health of Workers - Lucía Echeverría; J. Ignacio Gimenez-Nadal; José Alberto Molina (Institute of Labor Economics (IZA), 2022)
Research has shown that commuting is related to the health of workers, and that mode choice may have differential effects on this relationship. We analyze the relationship between commuting by different modes of transport and the health status reported by US workers, using the 2014-2016 Eating and Health (EH) Module of the American Time Use Survey (ATUS). We estimate Ordinary Least Squares models on a measure of subjective health, that is the self-reported assessment of individual general health status, and on the body mass index. We find that longer commutes by bicycle are significantly related to higher levels of subjective health and to lower body mass index, while commuting by walking is weakly related to both health measures. We test the robustness of our results to possible measurement errors in commuting times, to the exclusion of compensating factors, and to the estimation method. We additionally instrument individual use of bicycles with an indicator of individual green attitudes, based on the General Social Survey (GSS), and the results consistently show that individuals who commute longer by bicycle report better subjective health and lower body mass index. Our results may help policy makers in evaluating the importance of having infrastructures that facilitate the use of bicycles as a means of transport, boosting investment in these infrastructures, especially in large cities.
Keywords: R40; I10; J22; 330; commuting; health; walking; cycling; American Time Use Survey